2019
DOI: 10.21873/anticanres.13392
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Postoperative Pneumonia on Esophageal Cancer Survival and Recurrence

Abstract: Background/Aim: Postoperative pneumonia after esophageal cancer can lead to additional pain, prolonged hospital stay, and respiratory failure. These adverse events might lead to early recurrence and/or death. We investigated the influence of postoperative pneumonia on the esophageal cancer survival and recurrence after curative surgery. Patients and Methods: This study included 122 patients who underwent curative surgery for esophageal cancer between 2008 and 2018. The patients were classified into: i) those w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 15 publications
(17 reference statements)
1
18
0
Order By: Relevance
“…13 Several studies identify postoperative pneumonia as a predictor of short-term and long-term mortality after surgery. [14][15][16][17][18][19] Is there a difference in the outcomes of postoperative pneumonia between patients with and without T2DM?…”
Section: Introductionmentioning
confidence: 99%
“…13 Several studies identify postoperative pneumonia as a predictor of short-term and long-term mortality after surgery. [14][15][16][17][18][19] Is there a difference in the outcomes of postoperative pneumonia between patients with and without T2DM?…”
Section: Introductionmentioning
confidence: 99%
“…Elderly esophageal cancer patients generally have co-morbidities and age-related physiological problems (6)(7)(8). Previous reports have shown that the postoperative surgical complication rates after esophagectomy are 30% to 70%, and the mortality rate is 1%-5% (9)(10)(11)(12). Given this situation, perioperative management might be difficult in elderly esophageal cancer patients.…”
mentioning
confidence: 99%
“…Hospitals must balance the consumption of resources potentially needed for COVID patients with the potential harm to cancer patients if operations are delayed. As survival from esophageal cancer precipitously decreases with stage progression [ 15 , 36 , 37 ], we created a simple and informative model to estimate the potential harm to a patient with an early stage cT1b esophageal adenocarcinoma if his care was delayed due to the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…As COVID-19 is a new disease emerging in late 2019 there is no long-term follow up of patients available for reference. To approximate the effect of COVID-19 on overall survival after esophagectomy, we utilized available data on the impact of significant pulmonary complications after esophagectomy on 5-year overall survival [ 15 , 36 ]. The decrease in 5-year overall survival due to COVID-19 was set at 0.26 (range 0.1–0.35), and this was used to discount the cancer-related survival for each stage.…”
Section: Methodsmentioning
confidence: 99%